Design, synthesis, and biologic evaluation of novel chrysin derivatives as cytotoxic agents and caspase-3/7 activators - Al-Oudat BA; Alqudah MA; Audat SA; Al-Balas QA; El-Elimat T; Hassan MA; Frhat IN; Azaizeh MM (Dove Medical Press, 2019)
Buthina Abdallah Al-Oudat,1 Mohammad Ali Alqudah,2 Suaad Abdallah Audat,3 Qosay Ali Al-Balas,1 Tamam El-Elimat,1 Mohammad Abdelhafeez Hassan,1 Islam Nawaf Frhat,1 Marwah Mohammad Azaizeh2 1Department of Medicinal Chemistry and Pharmacognosy, College of Pharmacy, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of Clinical Pharmacy, College of Pharmacy, Jordan University of Science and Technology, Irbid 22110, Jordan; 3Department of Chemistry, College of Science and Arts, Jordan University of Science and Technology, Irbid 22110, Jordan Background: Chrysin (5,7-dihydroxyflavone) is a widely distributed natural flavonoid found in many plant extracts, honey and propolis. Several studies revealed that chrysin possesses multiple biological activities including anti-cancer effects. It has been established that activation of apoptosis is the key molecular mechanism responsible for the cytotoxic potential of chrysin. The objective of this study was to design and synthesize potent chrysin analogues as potential cytotoxic agents.Methods: A series of chrysin derivatives (3a-m) bearing N'-alkylidene/arylideneacetohydrazide moiety were designed, synthesized, and evaluated for their antiproliferative activity against two human breast cancer cell lines, MDA-MB-231 and MCF-7 by applying the MTT colorimetric assay. Selected compounds were tested for their ability to induce apoptosis through caspase 3/7 activation in MDA-MB-231 cells only since MCF-7 cells lack procaspase 3.Results: Compounds (3a-m) were obtained as geometrical isomers (E/Z isomers) in good yields upon treatment of hydrazide 5 with different aliphatic and aromatic aldehydes. Most of the synthesized compounds demonstrated moderate-to-good activity against both cell lines. The cytotoxicity results revealed the importance of lipophilic moieties at C-4 position of ring D in imparting the cytotoxic activities to the compounds. Compound 3e with 4-benzyloxy substituent was found to be the most active among the synthesized compounds with IC50 3.3 µM against MDA-MB-231 and 4.2 µM against MCF-7 cell lines. The cytotoxic potential of compound 3e is comparable to that of the well-known anti-cancer agent doxorubicin. In addition, compounds substituted with fluoro (3b), nitro (3h), and dimethylamino (3j) exhibited good cytotoxicity with IC50<6.5 μM against MDA-MB-231 and ,12 μM against MCF-7. Selected compounds were able to induce apoptosis in MDA-MB-231 cells as indicated by caspase-3 and/or -7 activation. Conclusion: Our results show that the newly designed chrysin derivatives exert anticancer activity in human breast cancer cell lines, MDA-MB-231 and MCF-7. Therefore, they can be considered as leads for further development of more potent and selective cytotoxic agents. Keywords: apoptosis, chrysin, design, synthesis, cytotoxicity, caspase-3/7, antiproliferative agents